(untitled) (International Journal of Engineering and Computer Science, 2016)
Smoothing filters have been widely used in image and video analysis. Also directional smoothers useful in motion analysis, edge detection, line parameter estimtion, and texture analysis. Such particular applications require the use of several different angles oriented directional filters. For real time applications, hardware devices having capability of parallel processing can be used. The steerability is the property, in which several filtering operations outputs are linearly combined to achieve output of a directional filter which is arbitrarily oriented. Smoothing filters has a property of steerability, which implies that the outputs of several filtering operations can be linearly combined in order to produce the output of a directional filter at an arbitrary orientation. There are several efficient FPGA implementations of the convolution operation for non-separable and separable have been presented in the literature, research on steerable filter implementations on FPGA is limited. In this paper, we present implementations of steerable Gaussian smoothers using VHDL and simulation is carried out using Model SIM software.